Pengaruh Holding Pressure dan Holding Time terhadap Defect Short Shot, Flash, dan Berat Produk Cap Gallon pada Proses Injection Molding - Amali, Moh. Husnul; Puspitasari, Etik (Universitas Lambung Mangkurat, 2024)
Plastic injection molding is a rapidly growing method of forming plastic materials in the modern era. The injection molding process is used to create gallon caps by melting plastic materials, but not always yield perfect results, resulting in defects. Short shot and flash defects are the most common defects during the mold-making process, affecting the product's weight. The purpose of this study is to determine the effect of variations in holding pressure and holding time parameters on short-shot defects, flash defects, and weight in gallon cap products. The presence of short shot and flash defects can lead to discrepancies in the weight of gallon cap products compared to existing standards. This method used an experimental research approach by varying the independent variables of holding pressure and holding time, with data processing done using the design of experiments method utilizing statistical software. The parameter settings for this testing included holding pressure variations of 240 bar, 265 bar, and 290 bar, along with holding time variations of 0.6 seconds, 0.8 seconds, and 1 second. The research results show that the independent variables and holding time significantly affect the dependent variables of short shot defects, flash defects, and the weight of gallon cap products. The ideal parameters for manufacturing gallon caps are using the injection molding process with a holding pressure of 265 bar, a holding time of 0.6 seconds, and a product weight of 10,627 grams, with no product defects such as short shot defects and flash defects observed in a single trial. This can enhance the quality and quantity of gallon cap production.